An innovative hapten and monoclonal antibody-based immunoassay for determining tebuconazole residues in aqueous samples. Issue 1 (1st January 2019) - Chen, Xiujin; Li, Zhaozhou; Sun, Fengxia; Cao, Xiaotian; Wang, Yao; Cao, Li; Gao, Hongli; Gao, Dong; Wang, Yawen
ABSTRACT: Tebuconazole is widely applied for controlling pathogenic fungi of crops and proved hazardous to human being. To better measure tebuconazole residues, an enzyme-linked immunosorbent assay for screening tebuconazole residues in aqueous samples was established using an innovative hapten (hapten1) designed via molecular model. The work concentration of calibration standard curves based on aqueous matrices ranged from 0.51 to 10.71 ng mL –1 . The cross-reactivities of other analogs were less than 6%. The detection limits of the assay were in the range of 0.197–0.297 ng mL –1 for tebuconazole in water samples. The average recoveries of tebuconazole in the spiked water samples varied from 76.76% to 107.52% with the variation coefficient scope of 4.54–13.26%. The obtained immunoassay was verified by gas chromatography coupled to mass spectrometry with high correlation coefficients ( r  > 0.9868). Herein, the proposed immunoassay offers a cost-effective, convenient, reliable tool for the determination of tebuconazole residues in aqueous samples.